Shaping the Digital Dissertation : Knowledge Production in the Arts and Humanities. - Kuhn, Virginia. (Open Book Publishers, 2021)
Shaping the Digital Dissertation aims to provide insights, precedents and best practices to graduate students, doctoral advisors, institutional agents, and dissertation committees. As digital dissertations have a potential impact on the state of research as a whole, this edited collection will be a useful resource for the wider academic community and anyone interested in the future of doctoral studies.